Knowledge, Attitude, and Precautionary Measures Towards COVID-19 Among Medical Visitors at the University of Gondar Comprehensive Specialized Hospital Northwest Ethiopia - Abate, Hailemichael (Infect Drug Resist, 2020)
BACKGROUND: Novel coronavirus disease 2019 (COVID-19) is an emerging respiratory disease caused by severe acute respiratory syndrome coronavirus. It was designated a public health emergency of international concern on January 30, 2020. COVID-19 has no effective treatment; nonetheless, early recognition of the disease and applying prevention strategies will help to mitigate the virus propagation. OBJECTIVE: This study aimed to assess the knowledge, attitude, and precautionary measures of medical center visitors at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia. METHODS: An institutional-based cross-sectional study was conducted from July 15 to August 15, 2020. A consecutive sampling technique was used to select the study participants. Data were collected by using a pre-tested structured, self-administered questionnaire. Data were analyzed using SPSS version 20. To explain the study variables, frequency tables, figures, and percentages were used. Bivariable and multivariable logistic regressions were used to see the association between independent and dependent variables. RESULTS: The prevalence of poor knowledge, attitude, and precautionary measures was 42.2%, 39%, and 41.6%, respectively. Being female (AOR=2.79, 95% CI=1.752–4.44), divorced (AOR=0.29, 95% CI=0.09–0.88), and residing in a rural location (AOR=1.93, 95% CI=1.07–3.26) were significantly associated with poor knowledge. Being female (AOR=95%, CI=1.21–2.98), a farmer (AOR=4.13, 95% CI=1.60–10.63), residing in a rural location (AOR=2.53, 95% CI=1.31–4.88), poor knowledge (AOR=2.38, 95% CI=1.52–3.72), and negative attitude (AOR=3.25, 95% CI=2.07–5.09) were significantly associated with poor precautionary measures. Increasing income in one unit of Ethiopian birr (ETB) (AOR=0.26, 95% CI=0.031–0.051) was significantly associated with negative attitude. CONCLUSION: The finding of this study showed that more than one-third of the participants had poor knowledge, attitude, and precautionary measures towards COVID-19 disease. A comprehensive health education program concerning knowledge, attitude, and precautionary measures toward COVID-19 ought to be strengthened.